Analysis of the Effectiveness of RSI and MACD Indicators in Addressing Stock Price Volatility - Melda, Melda; Mira, Mira; Nurlina, Nurlina (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
This research aims to compare the accuracy levels of the Relative Strength Index (RSI) and Moving Average Convergence Divergence (MACD) indicators in predicting stock volatility on the LQ45 index during the period from August 1, 2023, to July 31, 2024. The importance of this research is that it can provide research on the accuracy of the Relative Strength Index (RSI) and Moving Average Convergence Divergence (MACD) indicators, which can be a reference for capital market practitioners and stock investors in making more accurate and data-based investment decisions. The research method employs a comparative quantitative approach using secondary data in the form of stock closing prices. The analysis is conducted by calculating the accuracy of signals from both indicators using the accuracy formula and the Mann-Whitney test to determine significant comparisons. The results of this study indicate that RSI has an accuracy level of 97% with 31 successful signals out of 32 signals, while MACD has an accuracy level of 52% with 86 successful signals out of 166 signals. Statistical testing shows no significant difference between the two indicators (p = 0.522). Although RSI is more accurate, MACD is superior in generating returns in the long-term trend due to its sensitivity to small changes. This study concludes that RSI is more suitable for oversold and overbought market conditions, while MACD is effective for identifying momentum and long-term volatility direction. Future research suggestions could include combining other technical indicators for a more comprehensive analysis. These findings provide practical guidance for investors in selecting appropriate technical strategies for investment decision-making.